2012
DOI: 10.1007/s00268-012-1808-5
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Effectiveness of Ingunial Hernia Surgery in Northwestern Ecuador

Abstract: Inguinal hernia repair was cost-effective in western Ecuador through international collaboration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 62 publications
0
40
1
Order By: Relevance
“…All other interventions had a moderate or low strength of evidence. Disability weights for pediatric surgical conditions identified from the GBD studies [7, 8] and others [20, 38, 72, 97] ranged from 0.005 for finger amputation, to 0.850 for posterior sagittal anorectoplasty (Table 2). …”
Section: Resultsmentioning
confidence: 99%
“…All other interventions had a moderate or low strength of evidence. Disability weights for pediatric surgical conditions identified from the GBD studies [7, 8] and others [20, 38, 72, 97] ranged from 0.005 for finger amputation, to 0.850 for posterior sagittal anorectoplasty (Table 2). …”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21][22][23] Previous studies on the use of mosquito mesh in groin hernia repair have shown promising results with respect to tissue reaction, outcome, and cost-effectiveness. 19,[21][22][23][24][25][26] However, data from randomized trials are lacking to inform the safety and long-term effectiveness of this practice. The aim of the current randomized trial was to assess the outcomes of groin hernia repair performed with the use of a low-cost lightweight mesh as compared with a commercial lightweight mesh in a low-income country in sub-Saharan Africa.…”
mentioning
confidence: 99%
“…The recently published studies on the cost-effectiveness of hernia repair in disadvantaged countries [15,24,27,34] may represent a solution for the health policy of these countries when choosing the most costeffective procedure for hernia repair.…”
Section: Discussionmentioning
confidence: 99%
“…Western Pacific 258 37 15 22 Disease control priorities in developing countries. 2nd edition [34] World J Surg…”
Section: Discussionmentioning
confidence: 99%